Relationships between self-efficacy, parental attachment, peer attachment and aggression among adolescents in Selangor, Malaysia - Choy, Chiau Wei (2016)
Aggression has been recognized as a significant social problem worldwide especially when it is affecting the foundation of a country, which is the young generation. Due to the rising awareness on the severity of this chronic problematic behavior and increasing astonishing cases reported occasionally in Malaysia, more studies are imperative to identify the factors and remedies pertaining to this situation in order to effectively ameliorate this issue that has spread throughout the entire country. The manifestations of aggression among the younger generations nowadays have contributed several social problems such as substance abuse, antisocial problems, peer rejection and academic failure which each and every one of those must not be neglected by the society. Therefore, this study is essential and necessary to investigate the relationship between self-efficacy, parental (father and mother) attachment, peer attachment and aggression among adolescents in Malaysia. This study is a quantitative study and utilized a correlational design. Total of 471 adolescents aged 14 were selected from eight secondary schools in Selangor, Malaysia, recruited using multistage cluster sampling method. Data were collected using a self-administered questionnaire. The questionnaires consisted of the revised version of the Inventory of Parent and Peer Attachment (IPPA), Self-Efficacy Questionnaire for Children (SEQ-C) and Reactive-Proactive Aggression Questionnaire (RPQ).